2017
DOI: 10.3329/bjmm.v9i2.31422
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial isolates and drug susceptibility patterns of ear discharge from patients with ear infection at Shaheed Monsur Ali Medical College.

Abstract: Ear infection is a common problem for both children and adults especially in developing countries. However in Bangladesh particularly in the study area, there is no recent data that shows the magnitude of the problem. A retrospective study was conducted from from April, 2013 to March, 2014 at Shaheed Monsur Ali Medical College. Ear discharge samples were cultured on MacConkey agar, blood agar and chocolate agar plates. A total of 115 ear discharge samples were tested for bacterial isolation and 86 (74.78%) cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 9 publications
(10 reference statements)
5
10
0
Order By: Relevance
“…In this study, the predominant bacterial isolates were Staphylococcus aureus 43 (61.4%) followed by Pseudomonas spp., 13 (18.6%) which is similar to other studies (Akter et at., 2015;Prakash et al, 2013, and. However, in other studies in Ethiopia, predominant bacterial isolates were Proteus spp., followed by Staphylococcus aureus (Abera et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the predominant bacterial isolates were Staphylococcus aureus 43 (61.4%) followed by Pseudomonas spp., 13 (18.6%) which is similar to other studies (Akter et at., 2015;Prakash et al, 2013, and. However, in other studies in Ethiopia, predominant bacterial isolates were Proteus spp., followed by Staphylococcus aureus (Abera et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Current study showed significant difference on the prevalence of ear infection in genders. Females were more affected group (61.4%) than male (38.6%) similar findings were also reported by Hassan et al (2007) and Akter et al (2015). This may be due to ear cleaning habit of females.…”
Section: Discussionsupporting
confidence: 83%
“…This is comparable to the studies by Garima et al 4 , but much higher than Malkappa et al10; this may be due to prior antibiotic therapy. Out of the total samples cultured, 67.07% revealed single bacterial growth just like Garima et al 4 , Sonia Akter et al 7 The results of this study showed that Staphylococcus aureus (63.63%) was found to be the most predominant organism isolated in CSOM followed by Pseudomonas aeruginosa (10.90%) which is in agreement with the reports of some other investigators in different studies. 1,2,3,11,12 Antibiotic susceptibility patterns serve as a useful guideline for choosing the appropriate antibiotic.…”
Section: Discussionsupporting
confidence: 90%
“…4 Most of the microbiological studies of CSOM have revealed that the most common aerobic pathogen frequently found in CSOM are Staphhylococcus aureus, Pseudomonas, Gram negative organisms such as Proteus spp, Klebsiella spp, Escherichia coli, Haemophillus influenzae, and Moraxella catarrhalis. [6][7][8] Untreated cases of CSOM can result in a wide range of complications like persistent otorrhoea, conductive deafness, mastoiditis, labyrinthitis and facial nerve paralysis to more serious intracranial abscesses or thromboses. 4,5 Among these all these complications, hearing loss is the most common and preventable one.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Published data on chronic suppurative OM are difficult to find in developing countries and for that reason the optimal management of OM is still an unsolved problem. 5,29 Firstly, because there is no consensus on diagnostic criteria, 30 and secondly, a majority of the previous studies have focused on clinical diagnosis with little or no report on the microbiological etiology of OM. 31,32 There exists a dearth of knowledge on studies conducted on prevalence rates of OM in PLH in relation to microbiological examination.…”
Section: Introductionmentioning
confidence: 99%